The Resolution of Legal Disputes Regarding Administrative Violations During the Campaign Stage of Regional Head Elections Based on Law Number 7 of 2017 on General Elections - Agnes Visca Hemaskesuma Widodo; Moh Saleh (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2025)
Regional Head Election is one part of democracy and is a locomotive to carry out the mandate of reform where the people's power reaches to elect their Regional Head. However, the election of regional heads is rife with fraudulent practices, from money politics to disputes over results. So far, the focus of the spotlight on general election violations has been more on criminal sanctions, even though general elections are inseparable from administrative law. Then to what extent is the role of the organizing institution, especially election supervisors, to follow up on violations of the Regional Head Election. The duplication of handling administrative violations by the KPU and Bawaslu also needs to be improved. The KPU regulation, which states that the KPU is the reporter and reported party for alleged administrative violations, sounds strange, although it can be interpreted that this is a consequence of internal supervision at various levels between superiors and subordinates. Based on the description above, what is the action for administrative violations of the General Election, then related to the legal issues discussed in this study, namely how to identify administrative violations at the campaign stage of the Regional Head Election and what are the duties and authorities of the provincial election supervisory body regarding the resolution of administrative violations at the campaign stage of the Regional Head Election. Method The type of research used is normative research, and the data source from primary data is collected through literature studies and based on other legal books.